Measurement from sun-synchronous orbit of a reaction rate controlling the diurnal NOx cycle in the stratosphere - Walker, J; Dudhia, A (2011)
A reaction rate associated with the nighttime formation of an important diurnally varying species, N2O5, is determined from MIPAS-ENVISAT. During the day, photolysis of N2O5 in the stratosphere contributes to nitrogen-catalysed ozone destruction. However, at night concentrations of N2O5 increase, temporarily sequestering reactive NOx NO and NO2 in a natural cycle which regulates the majority of stratospheric ozone. In this paper, the reaction rate controlling the formation of N2O5 is determined from this instrument for the first time. The observed reaction rate is compared to the currently accepted rate determined from laboratory measurements. Good agreement is obtained between the observed and accepted experimental reaction rates within the error bars. © 2011 Author(s).